2014
DOI: 10.1016/j.ajpath.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Enhances HIV-1–Induced CD4+ T-Cell Apoptosis

Abstract: Substance abuse is a major barrier in eradication of the HIV epidemic because it serves as a powerful cofactor for viral transmission, disease progression, and AIDS-related mortality. Cocaine, one of the commonly abused drugs among HIV-1 patients, has been suggested to accelerate HIV disease progression. However, the underlying mechanism remains largely unknown. Therefore, we tested whether cocaine augments HIV-1-associated CD4(+) T-cell decline, a predictor of HIV disease progression. We examined apoptosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…Cocaine exposure is known to influence the function of immune cells. Cocaine can increase T-cell apoptosis, alter immune related miRNA profiles, change immune activation state, and impair lymphocyte proliferation 13 14 15 16 17 . However, little has been studied in terms of how drugs of abuse impact hematopoiesis.…”
mentioning
confidence: 99%
“…Cocaine exposure is known to influence the function of immune cells. Cocaine can increase T-cell apoptosis, alter immune related miRNA profiles, change immune activation state, and impair lymphocyte proliferation 13 14 15 16 17 . However, little has been studied in terms of how drugs of abuse impact hematopoiesis.…”
mentioning
confidence: 99%
“…Nonetheless, results in animal in vivo and in human in vitro suggest that illicit drugs (e.g., cocaine, marijuana, opiates) affect HIV viral replication [54-56]. In addition, high dose (200-1000 mg/L) cocaine has been shown to induce CD4+ T cell apoptosis in vitro [57], suggesting that drug may directly impair immune function and contribute to loss of virologic control. In the current study, we found that drug is independently associated with CD4+ T cell reconstitution in treated HIV disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis study involving 46 studies showed that cocaine abuse predominantly affects attention, impulsivity, verbal learning/memory, and working memory [7]. The mechanism by which cocaine causes cellular damage is complex, and has been associated with ER stress [8,9], apoptosis [10,11] and oxidative stress [12,13]. However, the exact mechanism of cocaine-induced neurotoxicity remains an area of interest.…”
Section: Introductionmentioning
confidence: 99%